Musik und kulturelles Gedächtnis - Assmann, Jan (Musik & Ästhetik, 2020)
The connections between music and memory are rich and manifold. This essay focuses on two manifestations of this: firstly, recourse to elements already presented at an earlier point in a piece (via ritornellos, reprises, leitmotifs and so forth), and secondly, recourse to other music and musical styles. The former activates a diachronic memory that decodes the meaning of a musical development through recollection and expectation, while the latter activates a cultural memory that understands what is heard via references to larger music-historical contexts.
Gesehen am 31.07.2020